Chlorogenic acid attenuates inflammation, oxidative stress, apoptosis and protects head kidney macrophage of yellow catfish from ammonia toxicity. (16th September 2021) - Jiang, Haibo; He, Kewei; Luo, Xueping; Zhang, Muzi; Shao, Jian; Gan, Lei; Lin, Yanhong; Qin, Chuanjie; Zhang, Hui; Wei, Qiwei
Abstract: Ammonia is the most common contaminants found in aquaculture water that seriously endangers fish health. However, there are few studies on the strategy and mechanism on alleviating ammonia toxicity in fish. The current study aimed to observe the cytotoxic effects of ammonia and the protective effects of chlorogenic acid (CGA) on head kidney macrophage of yellow catfish from the perspective of inflammation, oxidative stress and apoptosis. The cells were randomized into normal control, ammonia group (0.23 mg L −1 ), CGA group (125 µmol L −1 ), CGA (5, 25, 125 µmol L −1 ) + ammonia (0.23 mg L −1 ) groups. Cells were pretreated with CGA for 1 h followed by ammonia for 24 h. Findings suggested that ammonia treatment reduced cell viability, increased ROS production, up‐regulated antioxidant ( SOD, GPx ) and pro‐inflammatory ( TNF‐α, IL‐1, IL‐6, COX‐2, NF‐κB p65 ) genes expression, down‐regulated the mRNA levels of M2‐type macrophage marker ( Arg‐1 ) and anti‐apoptosis ( Bcl‐2 ), and CGA attenuated the toxic effects of ammonia. The findings may provide insight into the underlying mechanisms of ammonia toxicity and suggest that CGA can be used as a potential natural supplement to alleviate ammonia toxicity in fish.